Effect of fermentation methods on amino acids, fiber fractions and anti nutritional factors in different plant protein sources and essential amino acid index for Penaeus (Litopenaeus) vannamei - Jannathulla, R.; Dayal, J. Syama; Vasanthakumar, D.; Ambasankar, K.; Muralidhar, M. (Indian Journal of Fisheries, 2017)
The incorporation of plant protein sources in shrimp feed is limited due to unbalanced amino acids and higher anti-nutrients. In the present study, soybean meal (SBM), groundnut oil cake (GNC), rapeseed meal (RSM), sunflower oil cake (SFC) and guar meal (GRM) were subjected to natural, bacterial, fungal and yeast fermentation methods. The essential amino acid contents were increased by 4-28% in SBM, 7-26% in GNC, 3-27% in RSM, 8-18% in SFC and 4-14% in GRM. The increase was better for lysine with fungal fermentation (2.31-4.01%). The improvement in other limiting amino acids viz., methionine and tryptophan also showed positive response to fermentation. The analytical results showed improved essential amino acid index (EAAI) in the fermented ingredients and the increase was better with RSM (0.82 to 0.92) using Aspergillus niger. Fiber fractions were reduced (p